A multi-criterion fuzzy logic intra-cluster and inter-cluster-based stable cluster head election approach in large scale WSN. (2016) - Ranga, Virender; Dave, Mayank; Verma, Anil Kumar
Extending the lifetime of wireless sensor networks (WSNs) is a major concern in recent years. The main problem seems in the recent proposed approaches is that these use direct communication among nodes with the rotation of cluster heads (CHs) periodically to distribute energy consumption among various cluster heads (CHs). Energy saving mechanisms based only on metrics related to nodes' residual power cannot be directly applied to find stable CHs. The reason is that a sensor node or a CH having more residual power is willing to accept all requests, because it has enough residual battery power, therefore, much traffic will be injected to that node. In that case, a sharp decay of node's backup battery power. In this research paper, a multi-criterion fuzzy logic intra-cluster and inter-cluster based multi-hop routing protocol is proposed. The simulation results confirm that our proposed approach is more efficient than state-of-the-art approaches.